The mechanism of osseointegration on hydroxypatite (ha)-induced osteoblast stimulated with cytokines - Abdullah, Nurul Asma (Pusat Pengajian Kesihatan, 2015)
Advancement in oral implant research have led to remarkable transformation in osseointegration technology. ' However, current implants often encounter complications in its compatibility due to own immune rejection. Numerous surface coatings and growth factors have been widely explored to overcome these complications. Hydroxyapatite (HA) displays properties more likely to the mineral elements of human bones and hard tissues and is commonly used as a filler to replace bone or as a coating material. lnterleukins such as IL-6 and IL-17 which acts as key control in the immune response has been identified to have potential role in I bone metabolism. Understanding of bone metabolism implies the involvement of osteoprotegerin (OPG) and receptor activator of RANK ligand (RANKL) that balances the whole metabolism. RANKL stimulates osteoclastogenesis while the OPG regulates osteogenesis. This study aimed to understand the role of IL-6 and IL-17A in modulating OPG/RANKL system on HA-induced murine osteoblast cell line (MCT3T-E1). Treatments of IL-6 or in combination with IL-17A resulted in an increased expression of OPG and ALP, in contrast to RANKL expression; thus improved the OPG/RANKL ratio. In addition, bone mineralization process is indicated through up-regulation of ALP activity. Treatment of HA-induced osteoblast with IL-6 ± IL- 17A modulates the OPG/RANKL system, thus enhanced osteogenesis and bone remodeling process.